Umkämpftes Essen Produktion, Handel und Konsum von Lebensmitteln in globalen Kontexten - Reiher, Cornelia 1978-; Sippel, Sarah Ruth 1982- (Transnationale Geschichte, 2014)
This volume is based on empirical case studies from Europe, Asia and Africa, and analyzes the complex power relations in the global food system. The conditions behind the production, trading and consumption of foodstuffs are central themes of modern society. "The Competitive World of Food" analyzes the complex interests and power structures that determine the global food system. This is done using a number of case examples stemming from Europe, Asia and Africa, which are embedded in global relations. This volume shows that the global food system is increasingly being determined by privately financed companies and their specific interests. This makes a public and democratic debate about the future of food all the more important